ANALISIS STRATEGI FUNDRAISING ZAKAT DALAM MENINGKATKAN JUMLAH MUZAKKI Studi pada LAZ BaitulMaalKu Kabupaten Karawang - Nugroho, Arief; Ahmad, Ali; Wijoyo, Wirjo (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
The zakat fundraising strategy is an effort to collect zakat from individuals or business entities to achieve zakat goals. The main source of zakat fundraising is muzakki. So considering that the zakat fundraising process is fundamental to zakat management efforts, parties who have been given the authority to manage zakat must be able to convince the Muslim community about the importance of zakat. The fundraising strategy that has been implemented has not been able to achieve zakat potential and zakat fundraising targets in Karawang Regency. And the offline fundraising strategy has not been optimal in increasing the amount of funds and the number of muzakki in Karawang Regency. And this research is how the constraints in the fundraising strategy at LAZ BaitulMaalKu, Karawang Regency. This research uses qualitative methods, data collection with 3 methods, namely: observation, interviews, and documentation. After the data is collected, the next step, with the analysis stages, namely, data reduction, data presentation and drawing conclusions. The results of the research carried out are zakat fundraising strategies in increasing the number of muzakki at LAZ BaitulMaalKu, namely using 2 (two) strategies, the first is Direct Strategy (Offline) such as fundraising campaign, zakat pick-up services, and fundraising retail, namely the socialization and education of zakat to majelis taklim and companies. company. Second, the strategy is indirect (online) or indirectly, including through good friends channels, social media, through zakat accounts, and payroll or partnerships with corporations in Karawang. The strategy that is considered the most effective is the indirect strategy (online), namely payroll through the transfer of a partnership cooperation account with a corporation in Karawang. For factors driving the zakat fundraising strategy in increasing the number of muzakki at LAZ BaitulMaalKu, namely Institutional Legality, Monthly Compensation for the Elderly, Mustahiq empowerment programs, scholarships for dhuafa/outstanding students, and other programs that can make muzakki interested fulfill it in BaitulMaalku. While the inhibiting factor for the zakat fundraising strategy at LAZ BaitulMaalKu, namely knowledge about zakat in some communities is still lacking, some people believe more in religious figures and there are also people who channel directly, the Amil Zakat Institution is flourishing in the midst of society despite the legality of the institution. No, and the Islamic philanthropic institute LAZNAS is conducting fundraising in Karawang Regency.